Recht Vacuum of Arrangement for Digital Waste in Indonesia - Laot Kian, Antonius Maria (Magister Hukum Universitas Semarang, 2024)
The purpose of this study is to analyze the impact and solutions of the legal vacuum surrounding digital waste management in Indonesia. In this all-digital world, waste disposal can contribute 4% of carbon emissions, but there are no regulations that specifically regulate digital waste. This legal vacuum must be resolved immediately so that there is legal certainty for the independence of digital dignity in Indonesia. The method used is a type of normative legal research with a statutory approach (statute approach). The results showed that the legal vacuum (recht vacuum) in digital waste management caused impacts such as legal uncertainty, triggered legal chaos, and caused an increase in environmental pollution, so the solutions offered were: the government harmonized the law; the government issued the latest law on digital waste management; the community actively participated in the process of drafting laws on waste management digital; and the government and society must have legal awareness of the use of digital data.